Measurement and policy implications of NAIRU in SAARC countries - Shabbir Ahmad Gondal; Zakir Hussain; Rana Ejaz Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The study mainly focused on the estimation and implementation of the concept of nonaccelerating inflation rate of unemployment (NAIRU) in prominent SAARC countries (Pakistan, Bangladesh, India, Sri Lanka and Nepal) by using a panel dataset during 1971- 2012. Three approaches (i.e. the pooled OLS, the fixed effect, the random effect) were applied for empirical analysis. On the whole, the estimated values of NAIRU were reported 6.80 percent (with supply shocks) and 6.71 percent (without supply shocks) in these countries. The study also reported the values of NAIRU for Pakistan (6.73 percent), Bangladesh (7.85 percent), India (6.06 percent), Sri Lanka (6.04 percent) and Nepal (6.81 percent) separately. Furthermore, it was observed that when actual unemployment rate was below the reported value of NAIRU, there was a pressure on inflation rate to rise and vice versa (ceteris paribus) in these countries. The results were found significant in all the facets of the study. The study not only highlighted the policy implications but also suggested a comprehensive package of policy recommendations to address the problems of inflation and unemployment in SAARC countries.
Keywords: 330; NAIRU; Phillips curve; trade-off; inflation; unemployment; supply shocks